Bite the bullet ; Jon of Arts ; Silent war [videorecording] - Lazaro, Cheche (The Probe Team, 1989)
Tackles oil price increase, the Oil Price Stabilization fund established to support world fluctuation ; interview with Jon Santos being a new comedian, famous for impersonations ; and with Victor Corpus, a PMA instructor who joined the NPA, about his return to the Arm Forces of the Philippines.